Analisis Pengaruh Perubahan Suhu Batubara terhadap Nilai Total Moisture, Ash content, dan Nilai Kalori Batubara pada Area ROM Coal Stockpile di PT Mahakam Sumber Jaya - Indaswati Indaswati; Windhu Nugroho; Albertus Juvensius Pontus; Agus Winarno; Ardhan Ismail (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Coal stacked in stockpiles is directly exposed to sunlight and rain, which can significantly affect coal quality. These enviromental conditions influence the temperature of coal piles, subsequently causing fluctuations in moisture content. This stucdy investigates the effect of coal temperature on coal quality parameters at the ROM Coal Stockpile area of PT. Mahakam Sumber Jaya. Using actual field sampling methods with 30 samples collected form the ROM C HTS (High Total Sulphur) area during November – Desember 2024, coal temperature was measured using a thermogun and quality parameters total moisture, ash content and calorific value were analyzed using ASTM standard. Simple linear regression and correlation analysis were applied for data processing. Result showed that coal temperature has very stong negative correlation with total moisture (r = -0,89), a strong positive correlation with ash content (r = 0,59). The correlation between total moisture and calorific value was strong (r= -0,66). Temperature grouping into three ranges (30-50°C, 50-70°C, and 70-95°C) showed consistent trends: total moisture decreased by 2%, ash content increased by 1%, and calorific value increased by 66 kcal/kg as tempreture rose. These findings suggest that optimal coal tempreture maangement is essential to maintining coal quality during storage .